RISK FACTORS ASSOCIATED WITH THE OCCURRENCE OF TB IN HOUSEHOLD CONTACTS BASED ON SCREENING TESTS IN THE WORKING AREA OF THE KENARILANG PUBLIC HEALTH CENTER, TELUK MUTIARA DISTRICT, ALOR REGENCY - Djahari, Yohanes; Weraman, Pius; Syamruth, Yendris K.; Roga, Anderias Umbu (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Tuberculosis (TB) is one of the diseases with a high mortality rate in the world. Based on the Global Tuberculosis Report 2022, TB ranked 13th as the highest cause of death worldwide in 2019. TB transmission occurs through the air (airborne disease) increasing the possibility of infection to people who are physically close to TB patients, including those living in the same house. The infection rate can increase with the length of contact/exposure to TB patients. The possibility of TB bacteria to infect will increase when the immune system decreases, making humans susceptible to TB bacterial infection. This study aims to analyze the risk factors associated with the occurrence of TB in household contacts based on screening tests in the working area of the Kenarilang Community Health Center, Teluk Mutiara District, Alor Regency in 2023. The type of research is observational analytic using a cross-sectional design. Technique simple random sampling and sample as much as 157 respondents. Instrument study use questionnaire and use test Chi Square And regression multiple logistic (p=0.05).. The results of the study showed that factors related to the incidence of TB in household contacts were knowledge (p=0.001), attitude (p=0.001), availability of information (p=0.001), and residential density (p=0.001). Meanwhile, those that were not related were phlegm removal behavior (p=0.575) and cough etiquette (p=0.330). The factor most related to the incidence of TB was the level of knowledge (PR 98.4). The community, in this case, household contacts of TB, need to improve their knowledge and understanding of the dangers, prevention, and control of TB by accessing health information through health workers, print, and electronic media. The government needs to increase public knowledge by intensively promoting health about TB prevention through direct counseling and health promotion media.